Semiotic and film indexing in Brazil: a literature - Gatto, Ana Clara [UNESP]; de Almeida, Carlos Cândido [UNESP] (Universidade Estadual de Campinas, 2023)
Introdution: Information Science works with information recorded in support of the most varied types, and for its description and subsequent recovery, the process of indexing, reading and document analysis is carried out with the aim of identifying keywords that represent the subjects present in the document. Among the different types of documents, there are filmic documents, a combination of audio and moving image, in which other layers of meaning are present beyond the textual, such as cinematographic language, or editing, and techniques specific to cinema. Objective: The search sought to raise proposals that use cinematographic language as a form of documentary analysis and to present a mode of analysis based on Peircean semiotics. Methodology: Bibliographical research is used with a survey in the BRAPCI and Oasisbr databases with the aim of recovering Brazilian articles that deal with indexing film documents. Results: It is observed that the articles do not specifically deal with cinematographic language, since the way in which the film is organized and structured helps in identifying the subject, the use of semiotics is proposed as a way of identifying, in the different codes and in terms of, the subject addressed. Conclusion: Semiotics makes it possible to analyze parts as components of a whole, helping the indexer in the task of identifying the subject based on the link between character, space, time and location of the plot. Other possible research using semiotics is highlighted, such as the analysis of narrative videos and practices in the development of indexing methods and steps based on semiotics.
Semiótica e indexação de filmes no Brasil: uma revisão de literatura
Keywords: Audiovisual materials; Indexing; Semiology